👤

Rozwiąż równanie
[tex]\frac{1}{x+2} - \frac{2}{x} = \frac{x^{2-6} }{x^{2}+2x }[/tex]


Odpowiedź :

Odpowiedź:

[tex]\frac{1}{x+2}-\frac{2}{x}=\frac{x^2-6}{x^2+2x}\\\\\\x+2\neq 0\ \ \ \ i\ \ \ \ x\neq 0\ \ \ \ i\ \ \ \ x^2+2x\neq 0\\\\x\neq -2\ \ \ \ \ \ i\ \ \ \ x\neq 0\ \ \ \ i\ \ \ \ x(x+2)\neq 0\\\\x\neq -2\ \ \ \ \ \ i\ \ \ \ x\neq 0\ \ \ \ i\ \ \ \ x\neq 0\ \ \ \ i\ \ \ \ x+2\neq 0\\\\x\neq -2\ \ \ \ \ \ i\ \ \ \ x\neq 0\ \ \ \ i\ \ \ \ x\neq 0\ \ \ \ i\ \ \ \ x\neq -2\\\\D=R\setminus\left\{-2,0}\right\}[/tex]

[tex]\frac{1}{x+2}-\frac{2}{x}=\frac{x^2-6}{x^2+2x}\\\\\frac{1}{x+2}-\frac{2}{x}-\frac{x^2-6}{x^2+2x}=0\\\\\frac{1}{x+2}-\frac{2}{x}-\frac{x^2-6}{x(x+2)}=0\\\\\frac{x-2(x+2)-(x^2-6)}{x(x+2)}=0\\\\\frac{x-2x-4-x^2+6}{x(x+2)}=0\\\\\frac{-x^2-x+2}{x(x+2)}=0\\\\\frac{-x^2+x-2x+2}{x(x+2)}=0\\\\\frac{-x(x-1)-2(x-1)}{x(x+2)}=0\\\\\frac{-(x-1)(x+2)}{x(x+2)}=0\\\\\frac{-(x-1)}{x}=0\\\\\frac{-x+1}{x}=0\\\\-x+1=0\\\\-x=-1\ \ /\cdot(-1)\\\\x=1[/tex]

On Studier: Inne Pytanie